(untitled) (Dhaka University Journal of Science, 2012)
A 3-factor 2-level Yates pattern experimental design was used to develop a mathematical model for the alkylation of phenol with octanol-1 in the presence of sulphuric acid. A set of trials was planned with two replicates and the centre point trial with 4 replicates. Main effects as well as two- and three- factor interaction effects were statistically significant. The highest experimental yield was 79.5%. The experimental settings were temperature, 160ºC; molar ratio of phenol to octanol-1, 10:1; amount of 94% sulphuric acid, 8% by wt. of phenol; addition time, 2h and stirring time, 2h. Adequacy of the suggested model was checked. The difference between the experimental and estimated yield was negligible. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10339 Dhaka Univ. J. Sci. 60(1): 65-70 2012 (January)